Republic of Mozambique : Poverty Reduction Strategy Paper; Economic and Social Plan for 2005. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses Mozambique's Poverty Reduction Strategy Paper-Economic and Social Plan for 2005. In the international context, the paper presents the evolution of the international economy so as to understand under what economic conditions the country will have to implement its economic and social policy. It discusses the major macroeconomic objectives, and the evolution of the main economic indicators for Mozambique. The paper also presents the main policy measures to be implemented by the government, targets, and activities.